Taxonomic revision of the genus Gephyrellula Strand, 1932 (Arachnida, Araneae, Philodromidae) - Santos, Fabricio H.; Rheims, Cristina A. (Zootaxa, 2018)
Spiders of the family Philodromidae are free-living active predators, with laterigrade legs, eyes without tubercles, two tarsal claws and claw tufts. Although very common in zoological collections, their systematics is poorly known, especially in the Neotropics, and their specimens are usually identified only at family level. In this paper, the genus Gephyrellula Strand, 1932 is revised and the type species, G. violacea (Mello-Leitão, 1918) is redescribed and illustrated. Gephyrellula paulistana (Soares, 1943) is considered a junior synonym of G. violacea and thus, the genus becomes monotypic. In addition, the geographical distribution is extended and an updated distribution map is provided.